ANALISIS SEMIOTIK CHARLES SANDER PIERCE TENTANG TAKTIK KEHIDUPAN MANUSIA: DUA KARYA KONTEMPORER PUTU SUTAWIJAYA - Muhammad Wasith Albar (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2018)
This paper studies the representation of Man’s life-tactics in two works of contemporary fine arts by Putu Sutawijaya (2017) as a process of creative journey by a contemporary artist through his flashes of visual cultural ideas in curatorial Betwixt and Between. Life-tactics in here mean the ways in which an artist can swiftly execute society’s life’s problematics as representations of his succesful family’s strategy in the long run. The findings are obtained through triadic semiotic readings of Charles Sanders Pierce (Hoed 2007, Piliang 2018) and combined with historical method for contextualizing the creative processes of the artist.In two contemporary art works of Putu Sutawijaya, it is discovered that he always has consistent concept with full authority in his creative process based on his experiences which allow him to impose discourse and sublimation in the contemporary art in Indonesia. Then, following structurist analysis of Christopher Llyod (1993), it is discovered that Putu Sutawijaya’s sense of agency always implements silence attitude (Hindu concept of niharamkarah) in everyday human realities in sustaining and forming harmonious life. This statement can be recognized as represented in Survive 1, 2 and Pohon Kehidupan (Tree of Life).